Dewey and Lewin: A neglected relationship and its current relevance to psychology. (February 2018) - Colucci, Francesco Paolo; Colombo, Monica
In this paper, we explore the neglected relationship between Dewey and Lewin. Adopting a historical and theoretical perspective, we offer an interpretative framework for explaining why both scholars and their legacies may have been insufficiently recognized or misunderstood within psychology. Their relationship is discussed with particular reference to a common theoretical basis and conception of activity. The connections of their work with the Cultural Historical School and with Gramsci's thinking are suggested. We hold that from this perspective, Dewey and Lewin can be seen to contribute to contemporary psychology—action research in particular—by furthering its "emancipatory social relevance."